Predictive value of the systemic immune inflammatory index in cardiac syndrome x - Akin, Yusuf; Karasu, Mehdi; Deniz, Abdulmelik; Mirzaoglu, Cetin; Bolayir, Hasan Ata (Bmc, 2023)
IntroductionPatients with normal coronary arteries in whom increased vasospasm cannot be detected with the stress test should be evaluated in terms of cardiac syndrome x (CSX). Inflammatory systems are effective in endothelial activation and dysfunction in CSX. The systemic immune inflammation index (SII) is thought to be an important factor in determining the course of diseases, especially in infectious diseases or other diseases, as an indicator of the inflammation process. The aim of this study is to determine the role of SII levels in the diagnosis of CSX disease.MethodsThe study group included 80 patients who applied to the cardiology department of Firat University with typical anginal complaints between October 2021 and April 2022, and were diagnosed with ischemia after the myocardial perfusion scan, and then coronary angiography was performed and normal coronary arteries were observed.ResultsWhen the study and control groups were examined according to age, gender and body mass index, hypertension, smoking, diabetes mellitus, dyslipidemia and family history, no statistical significant difference was observed between the groups. It was observed that there was a significant difference between the high sensitive C- reactive protin levels of the individuals in the study and control groups (p = 0.028). SII levels measured in samples taken from patients were significantly higher than control subjects (p = 0.003). SII cutoff at admission was 582 with 82% sensitivity and 84% specificity (area under the curve 0.972; 95% CI:0.95-0.98;p < 0.001).ConclusionIt has been demonstrated that systemic SII parameters, which can be simply calculated with the data obtained from the complete blood count and do not require additional costs, can contribute to the prediction of CSX disease.
Keywords: Cardiac syndrome x; Systemic immune-inflammation index; Predictiveness